2004
DOI: 10.2466/pms.99.3.968-974
|View full text |Cite
|
Sign up to set email alerts
|

Visual Search Strategies of Soccer Players in One-on-One Defensive Situations on the Field

Abstract: This study analyzed visual search strategies of soccer players in one-on-one defensive situations on the field. The 8 subjects were 4 experts and 4 novices. While subjects tackled an offensive player for possession of the ball, their eye movements were measured and analyzed. Statistically significant differences between the visual search strategies of experts and novices showed experts fixated more often on both the knee and the hip regions of opponents than novices did. This suggests that information gained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…By foveating the door edges, the participants were better able to attend to the doors’ positions, while short fixation durations allowed the participants to process each door’s location more frequently. The differences in spatio-temporal patterns of fixation while walking or using a wheelchair seem to be similar to those between elite and non-elite athletes (Kato and Fukuda, 2002; Martell and Vickers, 2004; Nagano et al, 2004; Panchuk and Vickers, 2011), in that non-elite participants showed shorter fixation and more frequent saccades at critical moments.…”
Section: Gaze Behavior During Adaptive Locomotionmentioning
confidence: 59%
“…By foveating the door edges, the participants were better able to attend to the doors’ positions, while short fixation durations allowed the participants to process each door’s location more frequently. The differences in spatio-temporal patterns of fixation while walking or using a wheelchair seem to be similar to those between elite and non-elite athletes (Kato and Fukuda, 2002; Martell and Vickers, 2004; Nagano et al, 2004; Panchuk and Vickers, 2011), in that non-elite participants showed shorter fixation and more frequent saccades at critical moments.…”
Section: Gaze Behavior During Adaptive Locomotionmentioning
confidence: 59%
“…Drivers devote attention both to their own car and to the traffic around them, pedestrians focus on their path while avoiding obstacles [1], cooks devote attention to multiple pots and ingredients, athletes focus on the ball and on the opposing player [2], and lifeguards monitor children playing in different locations. Despite the ubiquitous need to distribute attention across multiple objects in our daily behavior, relatively few studies (e.g., [3], [4], [5], [6]) have examined the strategies people use when devoting attention to multiple objects simultaneously, and even fewer (e.g., [7]) have explored individual differences in the breadth of visual attention across these situations.…”
Section: Introductionmentioning
confidence: 99%
“…When a stressful situation occurs, the individual tries to solve the problem using various coping methods or by escaping from the stress source (Nagano, Kato, & Fukuda, 2004). One of the mechanisms of coping with stress is cognitive flexibility, which is defined as the ability to shift attention from one aspect to another (Hüttermann, Memmert, Simons, & Bock, 2013).…”
Section: Introductionmentioning
confidence: 99%